WASTE MANAGEMENT AND THE ROLE OF THE LOCAL COMMUNITY IN SUSTAINABLE BEACH TOURISM - Rahma Selvira Putri; Abdu Rahman (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This research aims to analyze the existing conditions of Akkarenna Beach as a coastal tourist attraction, to examine the forms of the Clean Tourism Movement (CTM) activities at Akkarenna Beach, and to assess its impact on both visitors and managers. The research method employed a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats) as suggested by Adrian et al. (2021). Primary data were collected through direct observation, in-depth interviews, and documentation, while secondary data were obtained from official reports and documents related to destination management. The findings reveal that Akkarenna Beach has significant potential to be developed as a sustainable tourism destination. Its key strengths include community-based management, relatively adequate facilities, and consistent environmental education programs. On the other hand, identified weaknesses include limited cleanliness monitoring systems, insufficient waste management facilities, and low levels of active tourist participation in environmental preservation. The implementation of CTM at Akkarenna Beach is realized through regular beach clean-up activities, socialization of reducing single-use plastics, and collaboration with environmental communities. These activities have had a positive impact on increasing visitor awareness of the importance of cleanliness, building a positive image of the destination, and strengthening the managers’ capacity to create environmentally friendly tourism. Moreover, the involvement of local communities in these activities reinforces the social dimension and expands multi-stakeholder collaboration networks. Future development strategies of CTM are directed toward strengthening synergy among government, private sector, academia, communities, and tourists. These efforts are supported by improvements in waste management infrastructure, the development of education programs based on sustainable tourism, and innovations in eco-friendly tourism products. With a holistic and participatory approach, Akkarenna Beach has the potential to become a model of community-based tourism destination that integrates environmental, social, and economic aspects in a balanced way to realize tourism sustainability.